2018
DOI: 10.12688/f1000research.16489.1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of women in Cambodia towards child physical abuse

Abstract: Background: This study attempted to explore the women’s attitude towards child physical abuse in relation to the respondent’s background factors, personal issues and autonomy. Methods: This was a cross-sectional study of 18,749 women of reproductive age (15-49 years) using 2010 Cambodia Demographic and Health Survey. Chi-square tests and bivariate analyses were performed. Results: A significant proportion of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Troublingly, prevailing social attitudes compound the problem. A recent study found that a significant proportion of women supported beating sons (69.2%) and daughters (67.2%) (Dalal et al, 2018).…”
Section: Civil Society and Government Discourse On Crc Implementationmentioning
confidence: 99%
“…Troublingly, prevailing social attitudes compound the problem. A recent study found that a significant proportion of women supported beating sons (69.2%) and daughters (67.2%) (Dalal et al, 2018).…”
Section: Civil Society and Government Discourse On Crc Implementationmentioning
confidence: 99%